Formation of magnesium silicate hydrate (M-S-H) at pH 10 and 50°C in open-flow systems. (January 2023) - Nishiki, Yuto; Cama, Jordi; Otake, Tsubasa; Kikuchi, Ryosuke; Shimbashi, Misato; Sato, Tsutomu
Abstract: Magnesium silicate hydrate (M-S-H) is a poorly crystalline Mg-silicate phase formed under alkaline conditions at low temperatures (T < 100 °C). Its formation has been studied in closed systems but not in open-flow systems, which better represent natural surface/subsurface environments. Here, MgO powder was used in reactions at pH ∼10 and 50 °C in flow-through experiments to study the formation of M-S-H as a function of aqueous Si concentration (1.5, 0.15, and 0 mM). Consumption of aqueous Si during precipitation of M-S-H resulted in an increase in the dissolution rate of the primary material (Mg hydroxide). Steady-state Si concentrations were used to calculate the dissolution rate of Mg hydroxide and the precipitation rate of M-S-H. Analyses of retrieved solids by electron microscopy and nuclear magnetic resonance spectroscopy confirmed the formation of M-S-H, although X-ray diffraction patterns provided no clear evidence of the presence of M-S-H because of the small amount precipitated and its nano-crystallinity. The chemical composition (Mg/Si ratio) of the M-S-H varied with the aqueous Si concentration of the injected solution. Mg/Si ratios of 1.00 ± 0.09 and 1.59 ± 0.15 were obtained with Si concentrations of 1.5 and 0.15 mM, respectively. Results indicate that the formation of M-S-H is feasible under Earth surface conditions, with dissolved silica coexisting with Mg-bearing minerals at alkaline pH. Graphical abstract: Image 1 Highlights: M-S-H formed at pH 10 and 50 °C in flow-through experiments. The chemical composition of the M-S-H formed depended on the aqueous Si concentration in the input solution. Mg oxide dissolution was promoted when aqueous Si reacted with dissolved Mg to form M-S-H.